“A crown of pure gold”: semicentennial anniversary of Moscow Theological Academy’s staying in the Trinity Lavra of St. Sergius in 1864 - Melkov Andrey Sergeevich (Studia Humanitatis, 2014)
In the connection of 200th anniversary jubilee of Moscow Theological Academy, the author has written the article, which describes half a century celebration of MTA’s staying in the Trinity Lavra of St. Sergius. Main achievements of the oldest Russian Theological school are named for the fifty-year period since 1814-1864, it is given the assessment of Academy’s contribution to the development of national theological education and divinity.